Revolution and journalism higher education in the Middle East/North Africa region - Schafer, Shaun T., author; Timpson, Bill, advisor; Davies, Tim, committee member; Kuk, Linda, committee member; Aoki, Eric, committee member (Colorado State University. Libraries, 2012)
The disruptions brought by the Arab Spring revolutions in the Middle East/North Africa (MENA) region in 2010-2011 created a series of personal and professional challenges for those involved in higher education in journalism in the region. This research uses narrative inquiry to examine the impact revolution had on a group of educators in the MENA region. The work reveals the impact of transportation woes, diminished student engagement, and personal considerations on a group of individuals involved in higher education in the region. The participants' work in journalism education receives additional consideration due to the restrictions on journalists prior to the Arab Spring and the uncertain space for journalists in the post-revolutionary environment.
Keywords: Arab Spring; higher education; journalism; revolution